The challenges and best practises for green office building in Putrajaya: the property managers’ perspective / Nur Aqilah Johari and Lizawati Abdullah - Johari, Nur Aqilah; Abdullah, Lizawati (2023)
Green office structures are intended to have a minimal impact on the environment and promote sustainability. However, property administrators in Putrajaya face unique challenges in maintaining these green structures. This research attempts to investigate the obstacles that contribute to the failure of green office building operations and maintenance and to identify the best practises adopted by property managers and maintenance teams in selected case studies. Literature categorises the operational and maintenance challenges of green office buildings into five categories: technical defects, financial problems, environmental and biological effects, social and cultural issues, and political and legal factors. The primary method for collecting data in this qualitative study is semi-structured interviews with property managers. The results highlight two significant obstacles: cost constraints and technical issues. Furthermore, the research identifies two significant best practices employed by property managers to effectively resolve these challenges: closely monitoring progress and implementing preventive maintenance plans to ensure the long -term efficiency and sustainability of green office buildings. Case study research focuses on two significant buildings in Putrajaya, Malaysia: Menara PJH and the Energy Commission Diamond Building. The importance of the selected case studies in providing valuable insights for property managers and maintenance teams in handling green office building challenges. The research outcomes could catalyze enhanced training, regulatory refinement, and broader adoption of effective strategies, driving the advancement of sustainability within Putrajaya's green office building sector.